2003
DOI: 10.1152/ajpgi.00160.2002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among the sevenHelicobacter pyloriproteins encoded by the urease gene cluster

Abstract: Survival of Helicobacter pylori in acid depends on intrabacterial urease. This urease is a Ni(2+)-containing oligomeric heterodimer. Regulation of its activity and assembly is important for gastric habitation by this neutralophile. The gene complex encodes catalytic subunits (ureA/B), an acid-gated urea channel (ureI), and accessory assembly proteins (ureE-H). With the use of yeast two-hybrid analysis for determining protein-protein interactions, UreF as bait identified four interacting sequences encoding UreH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 37 publications
6
100
0
1
Order By: Relevance
“…These comprised the following interactions: UreA with UreB, UreA with UreH, UreE with UreG, and UreF with UreH; the two latter interactions were confirmed by Y2H and co-immunoprecipitation (47). Phenotypes of insertion mutations in the corresponding urease genes in H. pylori were in agreement with their implication in urease activation (47,48). In addition, our data are consistent with biochemical data obtained for urease of Klebsiella aerogenes.…”
Section: Table I Tap-tagged Proteinssupporting
confidence: 90%
See 2 more Smart Citations
“…These comprised the following interactions: UreA with UreB, UreA with UreH, UreE with UreG, and UreF with UreH; the two latter interactions were confirmed by Y2H and co-immunoprecipitation (47). Phenotypes of insertion mutations in the corresponding urease genes in H. pylori were in agreement with their implication in urease activation (47,48). In addition, our data are consistent with biochemical data obtained for urease of Klebsiella aerogenes.…”
Section: Table I Tap-tagged Proteinssupporting
confidence: 90%
“…This complex is in agreement with our previous Y2H analysis that defined pairwise protein-protein interactions with some of the H. pylori urease proteins (16). These comprised the following interactions: UreA with UreB, UreA with UreH, UreE with UreG, and UreF with UreH; the two latter interactions were confirmed by Y2H and co-immunoprecipitation (47). Phenotypes of insertion mutations in the corresponding urease genes in H. pylori were in agreement with their implication in urease activation (47,48).…”
Section: Table I Tap-tagged Proteinsmentioning
confidence: 52%
See 1 more Smart Citation
“…Indeed, coexpression of the ureI, ureE, ureF, ureG and ureH genes was shown to be required along with structural genes ureA and ureB to yield fully active urease in E. coli (Cussac et al 1992). More recently, Voland and coworkers have shown that H. pylori ureE, ureF, ureG and ureH mutants are severely deficient in urease activity (Voland et al 2003). Among these four genes, the roles of ureE and ureG have drawn the most attention.…”
Section: Accessory Proteins For Urease Maturationmentioning
confidence: 99%
“…In addition to these nickel enzymes, H. pylori also possesses a NixA nickel specific permease (Bauerfeind et al 1996), accessory proteins UreIEFGH and HypABCDEF (some of which bind nickel) required for maturation or activation of the apoenzymes for the two nickel enzymes (Benoit et al 2004;Mehta et al 2003a;Olson et al 2001;Voland et al 2003), a nickel dependent regulator, NikR (Contreras et al 2003;van Vliet et al 2002), a recently identified nickel efflux system (CznABC) (Stahler et al 2006) and a histidine-rich heat shock protein, HspA, a GroES homologue Kansau and Labigne 1996). Here we address the roles and characteristics of these proteins, with emphasis on the roles of the accessory proteins directly required for Ni-enzyme maturation, and on the His-rich putative nickel storage proteins Hpn and Hpn-like.…”
mentioning
confidence: 99%